PRACTICING DEMOCRACY: UPHOLDING HUMAN RIGHTS AND THE RIGHT TO SOCIAL AND POLITICAL PARTICIPATION IN HONG KONG - Yuen, Mary (Asian Horizons, 2020)
This article examines the key elements of practicing democracy by people and rulers from the perspective of the Catholic tradition, with Hong Kong’s recent social movement as an example. It demonstrates how Hong Kong people practice democracy through political participation in a diversity of ways, through public rallies, art, singing, expression through their professions and affinity groups, and so on. However, the government failed to uphold the rule of law and the basic human rights of people, especially freedom of expression and protecting personal safety of people. This article also shows, during the social movement, how Catholic Church leaders, pastors, church organizations and individual Christians exercised their rights and responsibilities of political participation through a variety of means. At the end, the article points out that in the present situation, with a new national security law, the prospect of setting up authentic democratic structures of participation in Hong Kong is dimmed. However, Christians should not give up hope. Christians need to deepen their understanding of democratic values rationally, to feel the suffering of people with compassion affectively, and to keep practicing participation and solidarity in their daily lives. Strengthening the inner self through the practice of contemplation and joining faith and/or civic communities are important.